THE INTERDEPENDENCE BETWEEN THE FINANCIAL SECTOR AND BUSINESS SECTOR IN ASEAN 4 COUNTRIES - Aulia Keiko Hubbansyah; Zaafri Ananto Husodo (Journal of Indonesian Economy and Business (JIEB), 2018)
In this study, we analyze the dynamic interactions between the financial sectors and the business sectors in the ASEAN-4 countries (Indonesia, Malaysia, Thailand and Singapore). To do that, we apply the newly generalized version of the Vector Autoregressive Framework (VAR) spillover index approach proposed by Diebold and Yilmaz (2012) as our method of analysis. Based on quarterly data of each variable over the period from the first quarter of 1984 to the fourth quarter of 2015 for the ASEAN-4 countries, this study finds that: 1) Spillovers between the variables move in a diverse manner over the period of analysis for each country, 2) The variable that acts as the dominant crisis transmitter in each country is different for each country, 3) The interdependence between the variables became stronger, both within and across the countries, during the crisis period. In particular, the business sectors played a leading role during the onset of the crisis, while the financial sectors took their places as the dominant source of spillovers as the crisis deepened. 4) Credit growth in Thailand was found to be the dominant transmitter of shocks to the ASEAN-3 countries. Overall, these results suggest that the strength and movement of the spillovers between the financial and business sectors changed from time to time along with the changes that happened in the economies.